ANALISIS MIRROR PERDAGANGAN BARANG INDONESIA DENGAN THAILAND TAHUN 2018 - Suryono, Agus (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2020)
International trade is one of the country's foreign exchange sources. As a source of foreign exchange, many parties are involved in international trade, not only exportir, but also importir and government stakeholders from various countries. In fulfilling the needs of international trade statistics for policy, negotiation and main objectives of foreign exchange income, it is necessary to have the quality of international trade data that has certain standards. This analysis aims to determine the quality of trade in Indonesian goods with the trade of goods from Thailand, using the mirror analysis method. In addition, this paper also examines the reasons behind the incompatibility of export and import data from the two countries.To get a complete picture of this paper, the authors conducted a trade calculation between Indonesia and Thailand to get the differences between the two countries and present it with 2 digit Harmonize System (HS) and 6 digit HS details.